SATISFACTION OF INDIVIDUAL TAXPAYERS’ IN BANGLADESH - Ahmed, Shameem; Faisal, Md. Mahadi Masud (Australian Finance & Banking Review, 2021)
As a developing country revenue is necessary to accelerate the economic growth of Bangladesh. Besides, implementation of the tax law, individual taxpayers’ satisfaction will accelerate the collection of tax. The main objective of the study is to find out the impact of some determinants or factors which influence the overall satisfaction of the individual taxpayers’ of Bangladesh. In this study, quantitative data was gathered by taking personal interviews among 450 respondents and the response rate was 93.33%. Empirical tests using factor analysis and tests of hypothesis were performed in the study. The study incorporated three factors: tax rate, taxpaying system, and the behavior of tax employees. These three factors are considered to play a significant role in individual taxpayer satisfaction in Bangladesh. All the variables showed a significant and positive relationship between the independent variables and the dependent variable, taxpayers’ satisfaction. The study suggests some recommendations in order to increase the effectiveness of the tax collection rate by satisfying individual taxpayers’. JEL Classification Codes: H24.